SAT0655 Early endothelial damage in patients with raynaud's phenomenon. (15th June 2017) - Gualtierotti, R; Ingegnoli, F; Schioppo, T; Griffini, S; Grovetti, E; Borghi, MO; Cugno, M; Meroni, PL
Abstract : Background: Raynaud's phenomenon (RP) can be the first manifestation of systemic sclerosis (SSc) or other connective tissue diseases (CTDs), often preceding an overt disease by years. It is not known if markers of endothelial damage are detectable in those RP patients who subsequently develop a CTD. Objectives: We studied RP patients at their first evaluation to correlate the levels of endothelial markers with the subsequent development of an overt disease 36 months later. Methods: Eighty-two patients with RP at their first evaluation were recruited. We measured plasma levels of tissue-type plasminogen activator (t-PA) and von Willebrand factor (vWF), two markers of endothelial damage, and interleukin-6 (IL-6), a pro-inflammatory cytokine. Thirty healthy subjects served as healthy controls. Results: At baseline, 67 patients showed capillaroscopic normal pattern and 15 patients, of which 11 were very early SSc, had scleroderma pattern. Plasma levels of t-PA, vWF and IL-6 were higher in patients with capillaroscopic normal pattern (p=0.0001) than in normal controls and even much higher in patients with scleroderma pattern (p=0.0001). In patients with capillaroscopic normal pattern and RP of recent onset (<18 months), vWF plasma levels were higher when autoantibodies were present (p=0.020). After 36 months, among 48 RP patients with capillaroscopic normal pattern who remained in follow-up, 24 were diagnosed as primary and 24 as secondary RP. In secondary RP, basal levels of t-PA, IL-6 and particularly vWF were higher than in primary RP (p=0.005, p=0.004, p=0.0001 respectively) and normal controls (p=0.0001 for all). Conclusions: Our findings indicate that markers of endothelial damage are elevated in RP patients who subsequently develop SSc or other CTDs, even in the absence of capillaroscopic abnormalities. Disclosure of Interest: None declared